P562 Health seeking behaviour and acceptability of online outreach efforts among MSM using sex-seeking apps/websites. (14th July 2019) - Brennan, David; Kesler, Maya; Lachowsky, Nathan; Bekele, Tsegaye
Abstract : Background: Gay, bisexual, and other men who have sex with men (GBM) commonly use the Internet to find sexual partners and look for sexual health information. Little is known about online health information seeking behaviour and whether GBM welcome this information on socio-sexual apps/websites. Methods: GBM aged 14+ from Ontario were recruited into the #iCruise study via socio-sexual websites/apps from 07/2017-01/2018. Participants reported online health seeking behaviours and acceptability of sexual health information appearing as a clickable link/pop-up on socio-sexual apps/websites. Stratified by HIV status, multivariable logistic regressions were used to determine associations between sociodemographic variables and online health-seeking behaviour. Results: There were 910 GBM who were eligible for this baseline cross-sectional analysis. The majority reported being White (62%), and gay-identified (65%). A minority of participants were HIV-positive (12%), university educated (44%), and lived in rural areas (12%). Over two-thirds (69.3%, n=631/910) reported looking up online health information in the previous 3 months. Among HIV-negative/unknown status participants, online health seeking behaviour was negatively associated with older age (50+ vs <29, OR:0.35, 95%CI:0.23–0.55) and unknown HIV status (vs HIV-negative) (OR:0.57, 95%CI:0.39–0.84) and positively associated with more education (University vs High School OR:2.49, 95%CI:1.55–4.01). There were no significant associations among HIV-positive GBM. Having health information integrated into sex-seeking apps/websites was endorsed by 79% (agreed/strongly agreed). Acceptability via clickable link of health topics within sex-seeking apps/websites was very high: closest HIV/STI testing (96%); ASO website (93%); mental health information/resources (91%); public health/government website (90%); substance use information/resources (89%). Acceptability of a pop-up/reminder/notification with sexual health information such as how HIV is spread/how to prevent HIV transmission and safer sex practices to reduce HIV/STI transmission was also very high (86% and 89%, respectively). Conclusion: Acceptability of HIV and sexual health education information being embedded within dating apps/websites was very high and is currently an underutilized educational platform. Disclosure: No significant relationships.